Peran Infeksi Jamur dalam Memperparah Kerusakan Buah Kakao Akibat Serangan Helopeltis sp. - Toekidjo Martoredjo; Djungdjunan Ardy; Hermansyah Hermansyah; Tri Sunardi (Universitas Gadjah Mada, 1995)
Cocoa pod devastation caused by combine inoculations between pest and pathogen., either between Helopeltis theobromae and Botryodiplodia theobromae or between H. theobromae and Colletotrichum gloeosporioides, more sever than total single inoculation only by pest (H. theobromae) or pathogen (B. theobromae and C. gloeosporioides).